Accuracy, Preference, Comfort, and Chairside Time Using Digital Intraoral Scanner in Children: A Scoping review - Rahmi Ayu Budi Amalia; Indra Bramanti; Sri Budi Barunawati; Suryono; Ismianti (Postgraduate, University of Mataram, 2025)
This study aims to evaluate the accuracy, preference, comfort, and impression-taking time of digital intraoral scanners in children. Literature was sourced from Scopus, ScienceDirect, Wiley, and PubMed (2014–2024). From 124 identified articles, 22 were duplicates, and 11 met the inclusion criteria and were assessed using the CEBM Appraisal Tools. These 11 articles were included in the final analysis. Data were organized following the PRISMA Extension for Scoping Reviews guidelines. Results of the 11 studies, 3 concluded that digital intraoral scanners are more accurate than conventional methods, 3 found equivalent accuracy, and 5 did not evaluate accuracy. Five articles showed children preferred the digital intraoral scanner over conventional methods, while 6 did not address preference. Regarding comfort, 5 articles reported that children felt more comfortable using the digital scanner, 1 article reported equal comfort, and 5 did not evaluate comfort. For impression-taking time, 1 article reported faster scanning times, 2 reported longer times, 2 found similar durations, and 6 did not discuss impression time. Conclusion: Scientific evidence regarding the use of digital intraoral scanners in children remains limited. While their accuracy is generally comparable to conventional methods, children tend to show better preference and comfort. However, findings related to impression-taking time vary, indicating a need for further research using standardized instruments to draw definitive conclusions.